INTERNATIONAL PRACTICE OF PROFESSIONAL INTEGRATION OF PEOPLE WITH DISABILITIES: EDUCATIONAL PROGRAMS - Vasilyevich Ryabov, Victor; Vasilyevich Kirillov, Victor; Garifovich Rezakov, Ravil; Ilyinichna Muzafarova, Nelly (Revista Inclusiones, 2021)
Educational services to support employment and professional integration of people with disabilities are provided in many countries of the world. However, the models for providing such services in various countries are different. Currently, approaches to the professional integration of people with disabilities tend to shift from a medical model of rehabilitation to a model of workforce training focused on the opportunities of people and their participation. The study aims to analyze the international practice of educational opportunities for the professional integration of people with disabilities. The article highlights the relevance of studying the problem of professional integration of people with disabilities. An analysis of the main directions of the international practice of professional integration of people with disabilities in the countries of the European Union has been carried out. Special attention is paid to the professional integration of persons with disabilities through the mechanisms of university education in European countries.